2013
DOI: 10.1016/j.jcv.2013.06.042
|View full text |Cite
|
Sign up to set email alerts
|

Patient characteristics and severity of human rhinovirus infections in children

Abstract: HRV-C was the most prevalent species and on its own was associated with severe disease in children<3 years. The association between infection with HRV species and clinical presentation is complex and affected by many confounding factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

14
56
3
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(74 citation statements)
references
References 33 publications
14
56
3
1
Order By: Relevance
“…Interestingly, in the present pediatric study about 59.7% of picornaviruses infection cases are related to low respiratory tract infections (LRTIs) although these viruses are usually related to mild URTI. These results underline a need for picornaviruses investigation during viral diagnosis of respiratory tract diseases in light of recently published data regarding the association of rhinoviruses especially with severe respiratory tract infections in children [37][38][39], and in asthma exacerbations [16,[40][41][42].…”
Section: Authors' Contributionssupporting
confidence: 63%
“…Interestingly, in the present pediatric study about 59.7% of picornaviruses infection cases are related to low respiratory tract infections (LRTIs) although these viruses are usually related to mild URTI. These results underline a need for picornaviruses investigation during viral diagnosis of respiratory tract diseases in light of recently published data regarding the association of rhinoviruses especially with severe respiratory tract infections in children [37][38][39], and in asthma exacerbations [16,[40][41][42].…”
Section: Authors' Contributionssupporting
confidence: 63%
“…Significant differences between HRV-A and HRV-C were not found to be related to any of the patients' epidemiologic and clinical characteristics (Table 1). However, some series have shown that HRV-C could cause more severe disease in children younger than 3 years [6]. Respiratory viral codetections were found in four patients (two respiratory syncytial virus, one adenovirus, one human parainfluenza 3), which were not associated with either HRV species or severity, as reported previously [6].…”
supporting
confidence: 72%
“…Median PICU admission was 4 days (interquartile range 3.0-12.0 days). The most common HRV specie was HRV-C (18/35), followed by HRV-A (16/35), as reported by others [6]. Significant differences between HRV-A and HRV-C were not found to be related to any of the patients' epidemiologic and clinical characteristics (Table 1).…”
supporting
confidence: 59%
See 1 more Smart Citation
“…Only HRV was detected in P4-6, corresponding to moderate clinical symptoms (Table 1). It has recently been shown that asymptomatic individuals often harbor HRV (12), and Lauinger et al also reported that the HRV genotype per se was not linked to the severity of clinical symptoms (13). Data from the present study also support the notion that HRV infection is common among the human population.…”
supporting
confidence: 84%